If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5z + 3)(8 + z) = 0 Reorder the terms: (3 + 5z)(8 + z) = 0 Multiply (3 + 5z) * (8 + z) (3(8 + z) + 5z * (8 + z)) = 0 ((8 * 3 + z * 3) + 5z * (8 + z)) = 0 ((24 + 3z) + 5z * (8 + z)) = 0 (24 + 3z + (8 * 5z + z * 5z)) = 0 (24 + 3z + (40z + 5z2)) = 0 Combine like terms: 3z + 40z = 43z (24 + 43z + 5z2) = 0 Solving 24 + 43z + 5z2 = 0 Solving for variable 'z'. Factor a trinomial. (8 + z)(3 + 5z) = 0Subproblem 1
Set the factor '(8 + z)' equal to zero and attempt to solve: Simplifying 8 + z = 0 Solving 8 + z = 0 Move all terms containing z to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + z = 0 + -8 Combine like terms: 8 + -8 = 0 0 + z = 0 + -8 z = 0 + -8 Combine like terms: 0 + -8 = -8 z = -8 Simplifying z = -8Subproblem 2
Set the factor '(3 + 5z)' equal to zero and attempt to solve: Simplifying 3 + 5z = 0 Solving 3 + 5z = 0 Move all terms containing z to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5z = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 5z = 0 + -3 5z = 0 + -3 Combine like terms: 0 + -3 = -3 5z = -3 Divide each side by '5'. z = -0.6 Simplifying z = -0.6Solution
z = {-8, -0.6}
| 7sec(x)=7 | | 33.33t=-.25 | | -16-3c=5c | | 8343.8592=2*3.14*17.64+2*3.14*4.2*h | | -15n+8n+34-4=-65 | | 0.3z-62.1=3z | | -.1a=0 | | 15n+8n+34-4=-65 | | 6x-8x+5=-2x+-4+7 | | 1965.7656=2*3.14*54.76+2*3.14*7.4*h | | 15q+13q+8q=180 | | 3y=5-2y | | 3x+63+66=180 | | 20t+5t+5t=180 | | 3t+69+78=180 | | 1.4t+2.7=5.5 | | -25.294-0.8*-4.6=-3.2+2.7(2.7*-4.6+5.6) | | -8x-3=37 | | -25.294-0.8*4.6=-3.2+2.7(2.7*4.6+5.6) | | .5(x-1)=.33(x+1) | | x=0.5(10x-40) | | 72842.976=2*3.14*1281.64+2*3.14*35.8*h | | 8u-4u=19 | | D=150-10P | | (x-2)35= | | 5x^2-14x-96=0 | | 6sinx+1=0 | | 4x-15=5+2r | | 15-5w+2w=-2(-3w+2)+19 | | 630.0096=2*3.14*19.36+2*3.14*4.4*h | | (x)+(2x)=90 | | -80(-40+39)= |